Педагогічна діяльність професора Л.М. Славіна - Самойленко, Л.Г. (Археологія, 2007)
Статтю присвячено педагогічній діяльності члена-кореспондента АН УРСР професора Л.М. Славіна, засновника та першого завідувача (1944—1970) кафедри археології і музеєзнавства Київського державного університету ім. Т.Г. Шевченка. В статье изложены некоторые аспекты истории кафедры археологии и музееведения Киевского национального университета имени Тараса Шевченко, освещена педагогическая деятельность ее создателя и первого заведующего (1944—1970), члена-корреспондента АН УССР профессора Л.М. Славина. The article examines some aspects of the history of a department of archaeology and museum management studies at the National Taras Shevchenko University of Kyiv and illustrates the educational work of prof. L.M. Slavin, the department’s originator and its first head during 1944—1970, the corresponding member of AS USSR.